"Late" effectors from Leptosphaeria maculans as tools for identifying novel sources of resistance in Brassica napus. (5th August 2022) - Jiquel, Audren; Gay, Elise J.; Mas, Justine; George, Pierre; Wagner, Armand; Fior, Adrien; Faure, Sébastien; Balesdent, Marie‐Hélène; Rouxel, Thierry
Abstract: The Dothideomycete Leptosphaeria maculans, causing stem canker (blackleg) of Brassica napus, secretes different cocktails of effectors at specific infection stages. Some effectors ("Late" effectors) are specifically produced during the long asymptomatic phase of stem colonization. By manipulating their expression so that they are overexpressed during cotyledon infection (OEC transformants of the fungus), we previously postulated that resistance genes operating in the stem may be involved in gene‐for‐gene relationship and thus contribute to quantitative disease resistance (QDR). Here, we selected 10 relevant new effector genes, and we generated OEC transformants to screen a collection of 130 B. napus genotypes, representative of the available diversity in the species. Five B. napus accessions showed a typical hypersensitive response when challenged with effectors LmSTEE98 or LmSTEE6826 at the cotyledon stage, and all belong to the semi‐winter type of the diversity panel. In addition, five winter‐type genotypes displayed an intermediate response to another late effector, LmSTEE7919. These new interactions now have to be genetically validated to check that they also correspond to gene‐for‐gene interactions. In all cases, they potentially provide novel resources, easy to breed for, and accounting for part of the quantitative resistance in a species for which we are currently facing limited resistance sources. Highlight: Overexpression of "late" effector genes from Leptosphaeria maculans was used to screen a diversity panel of Brassica napus genotypes and allowed to identify novel resistances potentially contributing to quantitative resistance.